Worry and anger rumination in fibromyalgia syndrome - A. Ricci; S. Bonini; M. Continanza; M.T. Turano; E.M. Puliti; A. Finocchietti; D. Bertolucci (PAGEPress Publications, 2016)
The aim of the present study was twofold: 1) to investigate the psychological profile of patients with fibromyalgia syndrome (FS) as compared to patients with other chronic pain syndromes (CP) and healthy subjects (HS); 2) to examine the associations between anxiety, depression, worry and angry rumination in FS patients. FS patients (N=30), CP patients (N=30) and HS (N=30) completed measurements of anxiety, depression, worry and angry rumination. FS patients showed higher levels of state and trait anxiety, worry and angry rumination than CP patients and HS, and higher levels of depression than HS. Worry and angry rumination were strongly associated in the FS group. FS patients may use worry and rumination as coping strategies to deal with their negative emotional experience, which might impair their emotional wellbeing. Findings from the present study add to our understanding of the psychological profile of FS patients, and have important implications for developing a tailored CBT protocol for pain management in FS patients.